Oeuvres choisies ... Oeuv. [14] No. [1] de Ludwig van Beethoven. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Kriehuber, Josef, 1800-1876 (artist):::Contributor::::::::::::; Lämmel, Moritz (artist):::Contributor:::::::::::: (Hamburg; Germany; Schuberth & Co., 2022)
Mid-nineteenth century edition of the Piano Sonata no. 9 in E major, op. 14, no. 1, published by Schuberth & Co. as part of the "Oeuvres choisies de Ludwig van Beethoven."